The development of ambient TV in 2016 - Zheng, H.; Fu, Y.; Lugmayr, Artur (2012)
In this paper, we describe the potential trends of television industry in 2016. Now it seems that television has become an indispensable and critical smart terminal in ambient media researching field. After explaining the relation between ambient media and television industry, one consumer survey has been used to get more external opinions and subsequent predictions are obtained based on analyzing the survey. This paper is continuation report of the previous "Prediction TV in the year of 2013". © 2011 ACM.